2016
DOI: 10.1007/s11055-016-0299-5
|View full text |Cite
|
Sign up to set email alerts
|

Central Pattern Generators: Mechanisms of Operation and Their Role in Controlling Automatic Movements

Abstract: Central pattern generators consist of sets of interconnected neurons able to generate a basic motor output pattern underlying automatic movements (respiration, locomotion, chewing, swallowing, etc.) without any afferent signals from the executive motor apparatus. They are divided into constitutive pattern generators, which are active throughout life (the respiratory generator), and conditional pattern generators, which control episodic movements (locomotion, chewing, swallowing, etc.). As the motor output of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…In Fig. 5 we present for completeness the effect of changing the parameters E t , µ and τ f of the ED dissipation function dynamics, see (6). We find the generating principle to be robust, viz that the dependency of P close and P new on E t , µ and τ f is moderate.…”
Section: Robustness With Respect To Parameter Changesmentioning
confidence: 84%
See 1 more Smart Citation
“…In Fig. 5 we present for completeness the effect of changing the parameters E t , µ and τ f of the ED dissipation function dynamics, see (6). We find the generating principle to be robust, viz that the dependency of P close and P new on E t , µ and τ f is moderate.…”
Section: Robustness With Respect To Parameter Changesmentioning
confidence: 84%
“…It is well known that gaits and other regular muscle contractions, like breathing [6], are induced in many cases by central pattern generators [7,8], even though it is currently controversial whether this is the case for biped locomotion [9], viz for human walking. Abstracting from animal models, one may ask conversely to which extent compliant locomotion may be generated via self-organizing principles [10], that is in the absence of top-down control in the form of a central pattern generator.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches might narrow down the CNS region(s) generating the sequence, to be explored further using additional approaches. Such a CPG mindset may also draw attention to the extensive research on intrinsic and synaptic ion channel mechanisms that establish timing in traditional CPGs (Arshavsky et al, 2016;Harris-Warrick, 2010;Marder and Calabrese, 1996;Marder et al, 2014;Selverston, 2010) and the computational modeling of such CPGs that has revealed mechanisms likely to generate transitions between sequence elements (Ausborn et al, 2018;Grillner, 2006;Hao et al, 2011;Hull et al, 2016;Marder et al, 2014;Selverston, 2010;Shevtsova and Rybak, 2016). The roles of such mechanisms can then be explored for complex movement and nonmotor activity sequences, which may increase our understanding of their neural control.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the field of central pattern generation was born. In the years following, central pattern generators (CPGs; see Glossary) were demonstrated for a wide array of natural movements, including multiple forms of locomotion, breathing, scratching, calling, chewing, stridulating, digesting and copulating (Arshavsky et al, 2016;Delcomyn, 1980;Marder and Calabrese, 1996), although it was also recognized that sensory feedback modifies these basic movement patterns as needed, especially under rapidly changing environmental conditions. CPGs were found in vertebrates and invertebrates, for both episodic behaviors (like locomotion) and continuous behaviors (like breathing).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation